Assessing the Feasibility of an Edutech Startup: A Non-Financial and Financial Perspective: Mengevaluasi Kelayakan Sebuah Startup Edutech: Perspektif Non-Keuangan dan Keuangan - Qirbi Ibrahim; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2024)
This empirical study examines the viability of an edutech startup focused on skill enhancement for students and fresh graduates. Employing a mixed-methods approach, the research assesses both non-financial and financial aspects. The findings indicate that the venture is feasible in terms of management, resources, market, marketing, socio-economic factors, and technical operations. From a financial perspective, the venture shows promise with favorable indicators, including the payback period, profitability index, and average rate of return. These results have significant implications for addressing the skills gap in the edutech industry, improving graduate employability, and enhancing competitiveness in the job market. Highlights: The study utilizes a mixed-methods approach for a comprehensive evaluation of the edutech venture's feasibility. Both non-financial and financial aspects are examined, affirming the venture's potential for success. The research has broad implications for addressing the skills gap, improving graduate employability, and enhancing competitiveness in the job market. Keywords: Edutech Startup, Feasibility Assessment, Skill Enhancement, Graduates, Employability